Prev Next Index-> contents reference index search external Up-> CppAD Appendix Theory ForwardTheory SqrtForward Appendix-> Faq Theory glossary Bib Bugs WishList whats_new deprecated compare_c License Theory-> ForwardTheory ReverseTheory reverse_identity ForwardTheory-> ExpForward LogForward SqrtForward SinCosForward AtanForward AsinForward AcosForward tan_forward SqrtForward Headings

Square Root Function Forward Taylor Polynomial Theory
If   F(x) = \sqrt{x}    $F(x) * F^{(1)} (x) - 0 * F (x) = 1/2$  and in the standard math function differential equation ,   A(x) = 0 ,   B(x) = F(x) , and   D(x) = 1/2 . We use   a ,   b ,   d , and   z to denote the Taylor coefficients for   A [ X (t) ]  ,   B [ X (t) ] ,   D [ X (t) ]  , and   F [ X(t) ]  respectively. It now follows from the general Taylor coefficients recursion formula that for   j = 0 , 1, \ldots ,   $\begin{array}{rcl} z^{(0)} & = & \sqrt { x^{(0)} } \\ e^{(j)} & = & d^{(j)} + \sum_{k=0}^{j} a^{(j-k)} * z^{(k)} \\ & = & \left\{ \begin{array}{ll} 1/2 & {\rm if} \; j = 0 \\ 0 & {\rm otherwise} \end{array} \right. \\ z^{(j+1)} & = & \frac{1}{j+1} \frac{1}{ b^{(0)} } \left( \sum_{k=1}^{j+1} k x^{(k)} e^{(j+1-k)} - \sum_{k=1}^j k z^{(k)} b^{(j+1-k)} \right) \\ & = & \frac{1}{j+1} \frac{1}{ z^{(0)} } \left( \frac{j+1}{2} x^{(j+1) } - \sum_{k=1}^j k z^{(k)} z^{(j+1-k)} \right) \end{array}$ 
Input File: omh/sqrt_forward.omh